APLIKASI STRATEGI PRODUK, HARGA DAN PROMOSI PADA DEPOSITO BATARA IB DI PT BANK TABUNGAN NEGARA (PERSERO) KANTOR CABANG SYARIAH (KCS) MALANG - Firmansyah, Fani; Luthfiana, Anisa (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2013)
Third party funds in banking sector is a capital to carry out its business activities. Deposito Batara iB is one of the third party funds mudharabah mutlaqah. PT Bank Tabungan Negara (Persero) KCS Malang managed to get an increase in deposits to raise Batara iB in the last two years. In order to increase the fund, PT Bank Tabungan Negara (Persero) KCS Malang provide product strategy, pricing and promotions on Deposito Batara iB. This research was conducted using qualitative methods with the descriptive approach and the data collection techniques through interviews and documentation. Primary data obtained through interviews and documentation. Secondary data obtained from the object of research website. Data analysis using qualitative data analysis. Product strategy by creating a logo, motto and packaging in the form of features and services. Pricing strategy given PT Bank Tabungan Negara (Persero) KCS Malang by providing profit sharing ratio deposits, special provision (nisbah), does not apply administrative fees and penalty in their transactions. To introduce a Deposito Batara iB to customers, PT Bank Tabungan Negara (Persero) KCS Malang promote activities through various media. Use of advertising media, through personal selling, sales promotion and publicity. Keywords: strategi produk, harga dan promosi